A thermal decarboxylative Cloke–Wilson rearrangement of dispirocyclopropanes derived from para-quinone methides and bromo-Meldrum's acids: an approach to synthesize spirobutyrolactone para-dienones. Issue 18 (19th August 2020) - Li, Tong; Yan, Dandan; Cui, Chaoxing; Song, Xixi; Chang, Junbiao
Abstract : An unprecedented approach to synthesize spirobutyrolactone para -dienones from para -quinone methides and bromo-Meldrum's acids has been developed. Abstract : An unprecedented approach to synthesize spirobutyrolactone para -dienones from para -quinone methides and bromo-Meldrum's acids has been developed. A series of spatially congested dispirocyclopropanes are generated by spirocyclopropanation, and their unique reactivities have been explored for the first time in the thermal decarboxylative Cloke–Wilson rearrangement reaction. A variety of spirobutyrolactones are efficiently produced via the sequential spirocyclopropanation/rearrangement process in two steps with overall yields from 56 to 88%.